Analysis and Testing of U.S.-China Key Technology for Charging Interoperability of Electric Vehicles. Issue 1 (March 2021) - Zhang, X; Cui, J; Zhang, W; Ye, J D; Li, X L
Abstract: At present, China has overtaken the United States to become the world's largest new energy vehicle market. Due to differences in developmental trajectory, developmental mode, and charging standards, China and the U.S. have common interests and the foundation for cooperation, which can work together for a win-win development. Charging interoperability is the basis for ensuring charging safety and interchangeability of electric vehicles. This study examined and compared the differences between China and the U.S. in the standards for conductive AC charging of electric vehicles. The requirements for a control pilot circuit, proximity circuit, current capacity, and charging-state transition timing were analysed. Hierarchical and layered interoperability test cases based on GB/T 34657 and SAE J2953 series were presented. A dual interface interoperability test system was constructed and used to verify the test method rationale. The results provided a mutual inspection solution for AC charging equipment between China and the U.S. and accelerated global application and promotion of the electric vehicle industry.